Affective academic time management in the neoliberal university: From timeliness to timelessness - Valovirta Elina; Mannevuo Mona (Sage Publications, 2022)
In this article, we discuss affective time management discourses in academia. Drawing on our experiences of time management and brain fitness trainings at a Finnish university, we examine how the use and control of time are increasingly pressing societal and political matters affecting academic work globally. Time management training resources, such as guidebooks, websites and neuroscience-inspired staff training sessions, are seen as potentially fostering harmful productivity imperatives arising from the legacy of scientific work management doctrines. We argue that time-related affects, such as guilt and time poverty, need to be taken seriously to find the sustenance, such as a sense of collectivity, to persist through these counterproductive scenarios created by neoliberalist academic management styles.